Prevalence and type of anaemia in receptor negative breast cancer - Maraj, Amisha (My University, 2016)
Background Breast cancer is the most common cancer in women worldwide, with an incidence of approximately one million cases every year and is the main cause of cancer related deaths in women [1-3]. Breast cancers which are considered to be aggressive are triple negative breast cancers [4]. Triple negative breast cancer is known to have a worse prognosis and is associated with lympho-vascular invasion, higher recurrence rate and metastasis [4]. The reason behind this aggressiveness is not completely understood. Anaemia is common in breast cancer patients and may be a result of the disease process, complication of treatment or pre-existing co-morbidities [5-8]. Clinically significant anaemia is defined as a Haemoglobin level less than 10g/dL, and is accompanied by the symptoms and signs of anaemia such as fatigue, dizziness and pallor [9]. This degree of anaemia can result in a delay of initiating therapy as well as delay to correct the anaemia before initiating treatment such as neoadjuvant chemotherapy and surgery [10]. Furthermore, patients with anaemia with an Hb<10g/dL are known to blunt response to chemotherapy and radiotherapy due to tissue hypoxia [6]. The aim of this study is to determine the prevalence and type of anaemia in patients with triple negative breast cancer at Charlotte Maxeke Johannesburg Academic Hospital. Aim To determine the prevalence and type of anaemia in patients with triple negative breast cancer at Charlotte Maxeke Johannesburg Academic Hospital. Objectives 1. To study the demography of patients presenting with breast cancer. 2. To determine the prevalence of triple negative breast cancer. 3. To determine prevalence and type of anaemia in patients with breast cancer and whether this is affected by receptor status. Method This was a retrospective review of records of patients from the Breast and Endocrine Unit at Charlotte Maxeke Johannesburg Academic Hospital over 2002-2012 (11 year period). Once ethical approval was granted, data was obtained from the National Health Laboratory Services records of all breast cancer patients for the period 2002- 2012 (11 year period) at Charlotte Maxeke Johannesburg Academic Hospital. Patients demography, histological subtypes and profile was recorded as well as haemoglobin and mean corpuscular volume (Appendix 1). The data was recorded in Excel spreadsheets and the proportion of triple negative breast cancer patients with or without anaemia at the time of diagnosis (within 3 months) was compared using the chi-squared statistical tests to determine if a correlation exists. Age categories were expressed using the data sets of average (including standard deviation) and range. Gender was calculated as percentages and expressed as a ratio. Results Records of 520 patients were found; of which 94 patients were excluded. The average age was 55± 13.3 years (range 18-91). The female to male ratio was 109:1. Fifty two patients had triple negative breast cancer (TNBC) and 374 patients had receptor positive breast cancer (RPBC). Of these, only 246 patients had a haemoglobin level matched at time of diagnosis (within 3 months) that is 29 patients in the TNBC group and 217 patients in the RPBC group. Approximately 26% (65/246) of patients with haemoglobin level matched at time of diagnosis (within 3 months) had anaemia at the time of presentation. Anaemia was found to be more significant and prevalent in the TNBC group as 55.2% (16/29) of the TNBC group had anaemia whereas 22.6% (49/217) of the RPBC group patients were found to have anaemia at presentation. In the TNBC group, 16 of 29 patients had anaemia and microcytic and normocytic anaemia were equally common. Whereas, in the RPBC group, 49 of 217 patients had anaemia and normocytic anaemia was the most common i.e. 51% (25/49 patients). Conclusion Anaemia was found to be more common in patients with TNBC compared to RPBC. The predominant types of anaemia found in TNBC patients are microcytic and normocytic and may suggest different mechanisms. Within the TNBC group, microcytic and normocytic and macrocytic anaemia were 7/16 (43.75%); 7/16 (43.75%); and 2/16 (12,5%) respectively. Whereas, within the RPBC group, microcytic and normocytic and macrocytic anaemia were 22(44,89%); 25 (51.02%) and 2 (0.4%) respectively.
This research report was compiled to meet the requirements for a Master of Medicine in Surgery degree. The research report was submitted to the Department of Surgery at the University of the Witwatersrand. Johannesburg, 2015